IDENTIFICATION D'UNE ACTINOMYCETALE,PRODUCTRICE D’ANTIBACTERIENS, ISOLEE DE SOLS ARIDES DE LA REGION DE BISKRA. (Sciences & Technologie. C, Biotechnologies, 2006)
Fifty-five colonies are preleved following the catacteriticalaspect of Actinomycetales, from isolation mediums ensemenced by soil samples collected from desert region of Biskra. Ten strains were purified on selective medium with antifungal and anti negative Gram antibiotics. These strains produce bioactive substances against positive Gram and / or negative Gram bacteria. The strain A1with important spectrum of activity was identified with the cultural, morphological, physiological and biochemical characterisation as a member of Streptomycesgenera. It was considering belonging near to Streptomyces antibioticusand Streptomyces rochei.